Editorial Volume 51 Issue 2 - Cleveland-Innes, Martha (Canadian Journal of Learning and Technology, 2025)
This journal has always supported research about learning, technology, and change. In the evolving landscape of education places and spaces, one truth is still emerging: learning is not confined to a traditional classroom or dictated by curriculum. It is shaped significantly by communities small and large, technologies of many types, and the beliefs and actions of those who teach and learn. Recent studies from Canada, France, Switzerland, and the United States offer a view to the continuing transformational change. Outlined are the problems, the promise, and the increasing complexity of techno-pedagogical reality.